2015
DOI: 10.3389/fpls.2015.00183
|View full text |Cite
|
Sign up to set email alerts
|

Tall fescue cultivar and fungal endophyte combinations influence plant growth and root exudate composition

Abstract: Tall fescue [Lolium arundinaceum (Schreb.)] is a cool-season perennial grass used in pastures throughout the Southeastern United States. The grass can harbor a shoot-specific fungal endophyte (Epichloë coenophiala) thought to provide the plant with enhanced resistance to biotic and abiotic stresses. Because alkaloids produced by the common variety of the endophyte cause severe animal health issues, focus has been on replacing the common-toxic strain with novel varieties that do not produce the mammal-toxic alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 108 publications
(131 reference statements)
4
63
0
Order By: Relevance
“…Stands with higher endophyte-infection frequencies contain more soil C and N than E-stands or stands with low frequencies of infected tall fescue, presumably due to decreased microbial activity or altered plant inputs (Franzluebbers et al 1999;Guo et al 2015;Iqbal et al 2012). Therefore, because factors such as nutrient availability have been shown to influence nonsymbiotic N fixation in grassland soils (ZechmeisterBoltenstern and Kinzel 1990), non-symbiotic N fixing soil microorganisms may also be affected by CTE+ tall fescue, which has further implications for altered Npools and dynamics in pastures.…”
Section: Introductionmentioning
confidence: 99%
“…Stands with higher endophyte-infection frequencies contain more soil C and N than E-stands or stands with low frequencies of infected tall fescue, presumably due to decreased microbial activity or altered plant inputs (Franzluebbers et al 1999;Guo et al 2015;Iqbal et al 2012). Therefore, because factors such as nutrient availability have been shown to influence nonsymbiotic N fixation in grassland soils (ZechmeisterBoltenstern and Kinzel 1990), non-symbiotic N fixing soil microorganisms may also be affected by CTE+ tall fescue, which has further implications for altered Npools and dynamics in pastures.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that the alteration of plant metabolic responses during this stage correspond to the lifestyles of the microbe attempting to infect the plant tissues. For example, root exudate composition was found to vary with the type of endophytes colonizing tall fescue (Guo et al, 2015). Sugar and amino acid content in tomato root exudates have been shown to be differentially impacted by the application of biocontrol Fusarium sp.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the majority of metabolites used as signals between organisms in plant-microbe interactions are common to both mutualistic and pathogenic symbioses (Wong et al, 2019;Xu et al, 2015), there are also examples in the literature where either soil microbes or their plant hosts release genusor species-specific metabolites that facilitate their interaction. For example, root exudate contents of tomato and tall fescue vary based on the type of soil-microbes with which they were interacting (Guo, McCulley, & McNear, 2015;Kamilova, Kravchenko, Shaposhnikov, Makarova, & Lugtenberg, 2006). Similarly, soil-microbes can produce specific metabolites to facilitate root colonization on host plants; the secretion of hypaphorine by the ectomycorrhizal fungus Pisolithus tinctorius is related to colonization (Beguiristain & Lapeyrie, 1997).…”
mentioning
confidence: 99%